Kānphatthanā nư̄a dinpan læ nam khlư̄ap nai kāntham khrư̄angpan din phao khō̜ng lǣng Čhanthaburī - Sēksan Tanyāphirom (Mahāwitthayālai Būraphā, 2009)
Improvement of clay body and glaze used in pottery production in Chanthaburi Province, Eastern Thailand.